Unveiling Granulomatous Mastitis: Cytological Insights and Diagnostic Dilemmas of a Rare Breast Condition- A Five-Year Study - Goel, Seema; Singla, Aashima; Pendharkar, Devyani; Devra, Anshu Gupta (Journal of Neonatal Surgery, 2025)
Granulomatous Mastitis (Gm) Is A Rare Benign Inflammatory Disorder Of The Breast, Characterized By The Presence Of Painful Lumps. It Primarily Affects Young Women, Who Often Report A History Of Antibiotic Use That Does Not Provide Significant Relief. Gm Can Be Classified Into Two Categories: Idiopathic And Specific. Due To Its Clinical And Radiological Presentation, Which Closely Resembles That Of Breast Malignancy, Gm Should Be Included In The Differential Diagnosis Of Chronic Mastitis. Aim And Objectives: This Study Aims To Thoroughly Evaluate The Cytomorphological Characteristics Of Gm, Highlight Its Key Clinical Features, And Effectively Differentiate It From Conditions That Mimic Breast Carcinoma, Thereby Preventing Unnecessary Mastectomies. Materials And Methods: A Retrospective Observational Study Was Conducted Over Five Years At Smsr, Sharda University, Involving 15 Confirmed Cases Of Gm. Aspirates Were Stained Using Giemsa Stain, And Special Stains, Including Ziehl-Neelsen And Pas, Were Employed To Exclude Mycobacterial Or Fungal Etiologies. Results: The Study Reviewed 15 Cases Of Gm, With A Mean Age Of 29.2 Years. Notably, Left Breast Involvement Was Found In 53% Of The Cases, While Overlying Skin Inflammation Was Observed In 60%. Histopathological Examination Consistently Revealed Non-Caseating Granulomas Along With A Significant Presence Of Polymorphs In The Background, Indicating Gm. Importantly, Tuberculosis Was Confirmed In 40% Of The Cases, And Additional Ancillary Tests Further Supported The Diagnosis. Conclusion: Gm Poses A Complex Challenge For Diagnosis And Treatment Due To Its Rarity And The Necessity To Differentiate It From Other Causes Of Mastitis And Breast Malignancies. Timely And Accurate Diagnosis Is Essential To Prevent Unnecessary Mastectomies And Ensure Appropriate Management.